Integrating Da’wah into Islamic Counseling Practices on Social Media Platforms - Nurul Faizah Kamaruddin; Siti Aminah; Sinta Rahmatil Fadhilah; Nura Arabi (Scidacplus, 2026)
This study explores how da’wah can be positioned as an Islamic counseling approach within social media environments. The growing use of digital platforms has not only changed communication patterns but also intensified psychological and emotional challenges such as anxiety, stress, and identity confusion. These conditions call for counseling approaches that are both accessible and spiritually grounded. This study employs a qualitative descriptive design using a library research method, drawing on recent scholarly works related to da’wah, Islamic counseling, and digital media. The findings show that integrating da’wah into counseling practices supports the development of self-awareness (muhasabah), encourages personal transformation (hijrah), and strengthens spiritual resilience (taqwa). In this context, social media functions not merely as a communication tool but as a space for ongoing guidance and interaction. This study suggests that da’wah can play a more integrative role as a counseling approach in addressing contemporary psychological and spiritual needs in the digital era.